Digital demand and digital deficit: conceptualising digital literacy and gauging proficiency among higher education students. Issue 3 (4th May 2022) - Morgan, Ashlee; Sibson, Ruth; Jackson, Denise
ABSTRACT: For higher education students, developing digital literacy enhances their value to future employers and appeal in the graduate labour market. The purpose of this study was two-fold. First, to provide a tridimensional (technical, cognitive and etiquette) conceptual framework and definition of digital literacy. Second, to investigate students' ( N = 324) perceptions of their digital literacy proficiency through an online survey. Multiple linear regression revealed mixed results for different aspects of digital literacy. Students reported the lowest proficiency in using digital information, specifically in terms of evaluation and determining bias and quality of information. The highest levels of proficiency were for social literacy skills, such as communicating appropriately online. There were minor differences between genders, while work experience and length of time in higher education had positive impact. Findings highlight the need for increased focus on digital literacy adaptability and industry-relevant experience within curriculum.